How graduate students are supported in their teaching: What the literature does and does not tell us. (11th April 2016) - Hoessler, Carolyn; Stockley, Denise
Abstract : Purpose: – To provide a cohesive framework for understanding how supports co-occur and interact to impact graduate students' teaching experiences, this paper systematizes the multi-layered context in which institutions, departments, faculty, peers, and individuals provide support. Previous studies on graduate students' teaching focussed on specific programs, initially to describe them, and more recently to assess their outcomes. However, this piecemeal approach misses the complexity of graduate students' contexts. Design/methodology/approach: – Through a literature review of existing supports for graduate students' teaching, the need for a contextual framework was clearly identified leading to its development and application to provide a cohesive categorization of supports. Findings: – The review of existing literature identified graduate students' supports and needs for support across all layers of their higher education context. Practical implications: – This new framework offers a theoretical grounding for teasing apart the intertwined influences on graduate students' teaching development. Higher education professionals seeking to demonstrate value for money may be disappointed by evaluations of formal programming revealing lower than expected changes in practice despite promising growth in graduate student's conceptions of teaching. By considering additional influences and barriers to graduate students implementing newly learned teaching practices, potential conflicts may be revealed and addressed, and enabling influences identified and increased. Originality/value: – Missing from existing literature is consideration of the multiple co-occurring influences on graduate students' development, and an examination of how the various sources of support interact. This framework reveals potential interactions and contradictions that are important to consider when creating and evaluating supports for graduate students' teaching.